IDENTIFICAÇÃO MOLECULAR DA EHRLICHIA CANIS, BABESIA SPP., ANAPLASMA PLATYS E HEPATOZOON SPP. EM CÃES ANÊMICOS ATENDIDOS NO HOSPITAL VETERINÁRIO DA UFPB - Fernandes, Magda (2017)
Anemia is a clinical and laboratory change in multifactorial causes. Hemoparasites are considered to cause anemia by several mechanisms. The objective of this work was to identify Ehrlichia canis, Babesia spp., Anaplasma platys and Hepatozoon spp. in animals with anemia attended at the Veterinary Hospital of the Federal University of Paraíba (UFPB). A total of 95 blood samples were selected from anemic animals, which were submitted to DNA extraction and polymerase chain reaction (PCR) for the detection of Ehrlichia canis, Babesia spp., Anaplasma platys and Hepatozoon spp. Direct search for hemoparasite, when requested by the veterinarian, was performed at the Laboratory of Clinical Pathology of the Veterinary Hospital. In PCR, Hepatozoon spp. in 67.3% of the animals, Babesia spp. in 45.3%, E. canis in 31.6%, and A. platys in 10.5% of the animals. The involvement of two hemoparasites was found in 32.6% of the infections. Simultaneous infection by three hemopasites was identified in 16.8% of the animals. Direct hemoparasite screening showed false-negative and false-positive PCR results. The use of PCR contributes to the definitive diagnosis of cases of hemoparasitosis in the animals treated at the Veterinary Hospital of the UFPB.